Model Time-Cost Trade-Off pada Pekerjaan Tangga Beton Di Banda Aceh - T. Muhammad Fachrul Rozie; Fachrurrazi Fachrurrazi; Cut Zukhrina Oktaviani (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2021)
The construction project is very dependent on the project management process, both costs and time. In the implementation process, the service provider must complete one job before doing the next work. Addressing this problem requires a method that is accelerated. The purpose of this study is to do time-cost trade-off modeling. The model wa devoloped from respondent’s perceptions through filling out questionnaires and RAB data. Respondents in study ware directors, estimators and project manager at construction companies domiciled in Banda Aceh. The results showed that ladder work can be broken down into formwork, cleaning and casting. Based oo sub-activities, ladder work can be accelerated from the normal duration of the projectwith the maximum additional cost arisisng from the acceleration of the duration of the ladder work is Rp. 14.109.984,07 (22,13% of normal costs), the maximum additional cost incurred due to the acceleration of the duration of the casting work is Rp. 12.144.740,00 ((18,78% of normal costs) and the maximum additional cost incurred due to the acceleration of the duration of the formwork work is Rp. 12.331.359,00 (19,64% of normal costs). Additional costs per day vary for work items on the stairs because the time-cost trade-off model is non-linear.